Preoperative anxiety and depression: differences among patients submitted to the first cardiac surgery - Kazitani, Bruna Sonego (2018)
Objective: to compare the preoperative symptoms of anxiety and depression among patients submitted to the first cardiac surgery. Methods: observational, analytic and cross-sectional study. A consecutive and non-probabilistic sample consisted of patients submitted to elective cardiac surgeries, without clinical decompensation on the day of the interview. To assess the anxiety and depression symptoms, the Hospital Anxiety and Depression Scale was used. The symptoms were compared by means of the Mann-Whitney test, α=5.0%. Results: the study participants were 80 patients submitted to the first surgery and 19 to reoperation. Patients in their first surgery presented a median score of six and reoperated patients a median score of four on the depression scale (p=0.107). Concerning the anxiety symptoms, patients in their first surgery presented a median score of eight, against six for the reoperated patients (p=0.171). Conclusion: the anxiety and depression scores were higher among the patients submitted to their first surgery, but no statistically significant difference was found between the groups.